2009
DOI: 10.1111/j.1365-2672.2009.04174.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity ofConiothyrium minitansand its macrolide antibiotic macrosphelide A

Abstract: Aims:  Assessment of antimicrobial activity of the mycoparasite Coniothyrium minitans and its macrolide antibiotic macrosphelide A. Methods and Results:  Thirteen isolates of C. minitans were tested for ability to inhibit a number of filamentous fungi, yeasts, oomycetes and bacteria in agar based tests. Activity was found against some ascomycetes, basidiomycetes, oomycetes and Gram‐positive bacteria, but not against zygomycetes, yeasts or Gram‐negative bacteria tested. Six C. minitans isolates (Conio, Contans,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
(49 reference statements)
0
20
1
Order By: Relevance
“…The results also showed that conidiation of an L-arginine auxotroph could be restored by the NO donor SNP, but not by cGMP. Thus, NO-mediated conidiation has more than one signal pathway, including the cGMP signal pathway and another yet-unknown pathway, and both are essential for conidiation in C. minitans.Coniothyrium minitans is a sclerotial parasite of the notorious plant pathogen Sclerotinia sclerotiorum, and its potential for biological control of Sclerotinia diseases has been well demonstrated in several countries (13,17,21,28,33,34,36,37). Efficient production of conidia will further enhance the potential of C. minitans as a biological control agent.…”
mentioning
confidence: 99%
“…The results also showed that conidiation of an L-arginine auxotroph could be restored by the NO donor SNP, but not by cGMP. Thus, NO-mediated conidiation has more than one signal pathway, including the cGMP signal pathway and another yet-unknown pathway, and both are essential for conidiation in C. minitans.Coniothyrium minitans is a sclerotial parasite of the notorious plant pathogen Sclerotinia sclerotiorum, and its potential for biological control of Sclerotinia diseases has been well demonstrated in several countries (13,17,21,28,33,34,36,37). Efficient production of conidia will further enhance the potential of C. minitans as a biological control agent.…”
mentioning
confidence: 99%
“…This phenomenon is similar to pH-regulation of fumonisin biosynthesis in F. verticillioides, in which pac1 was found to repress fumonisin biosynthesis under neutral ambient pH (Flaherty et al 2003). Tomprefa et al (2009) indicate that AFS or macrosphelide A produced by C. minitans can inhibit mycelial growth of many plant pathogenic fungi including Botrytis spp., Cladosporium cucumerinum, Fusarium oxysporum, Sclerotinia spp., Sclerotium cepivorum, Penicillium nigricans, Phytophthora nicotianae, Pythium ultimum and Rhizoctonia solani. Of these fungi, Sclerotinia spp.…”
Section: Discussionmentioning
confidence: 75%
“…As commented by the EFSA BIOHAZ Panel, available information illustrate the potential of C. minitans to be involved in biocontrol strategy and concern the key role associated to macrosphelide A in the antimicrobial activity of C. minitans (Tomprefa et al, 2009;EFSA BIOHAZ Panel, 2010, 2013. Available information suggests that secondary metabolites/toxins are involved in the mode of action of mycoparasitism.…”
Section: Secondary Metabolites/toxinsmentioning
confidence: 99%
“…This investigation may also be important in relation to efficacy, as inhibition of Bacillus thuringiensis and Bacillus subtilis has been demonstrated, indicating a possible incompatibility with other microbial plant protection products (Tomprefa et al, 2009). Therefore, data on the potential for C. minitans Strain CON/M/91-08 to produce metabolites in relation to these criteria are necessary to assess if the further data requirements and the corresponding risk assessment according to Commission Regulation (EU) No 283/2013, part A, section 7 (standard data requirements and assessment mandatory for chemical plant protections active substances) are triggered.…”
Section: Fate and Behaviour In The Environment Of Any Relevant Metabomentioning
confidence: 99%